PENGEMBANGAN FARMASIPRENEUR TABLET TAMBAH DARAH BERBAHAN DASAR FERRO SULFAT DARI SCRAP BESI BENGKEL BUBUT UNTUK SISWA SMK - Soebiyanto; Nur Hidayati; Lucia Sincu Gunawan; Muhammad Dzakwan; Ilham Kuncahyo; Ana Indriyati; Nicolay Wening Audrey; Sunardi; Argoto Mahayana; Bimo Putranto; Sumardiyono; Mahardira Dewantara; Afif Afghohani (LPPM ITB AAS Indonesia Surakarta, 2025)
The partner in this Community Service Program is the Mandala Bhakti Health Vocational School, Pharmacy Department, located at Jalan Singosari Utara II, Nusukan Village, Banjarsari District, Surakarta City. Iron deficiency is a common nutritional problem, especially among adolescents. Scrap iron waste from machine shops has the potential to be used as a source of ferrous sulfate for the manufacture of iron supplements. This activity aims to develop iron supplement tablets from ferrous sulfate synthesized from iron scrap, ensure their safety through heavy metal testing, and enhance pharmaceutical entrepreneurship knowledge (pharmaceutical entrepreneurship) among vocational high school students. A total of 20 vocational high school students were involved in training that covered ferrous sulfate synthesis, tablet formulation, and product marketing strategies. Evaluation was conducted through pre-tests and post-tests, as well as heavy metal contamination analysis (Pb, Cu, Cd). The results showed a significant increase in knowledge, with an average pre-test score of 70 and a post-test score of 100. Heavy metal analysis showed no contamination (Pb: 0 ppm, Cu: 0 ppm, Cd: 0 ppm), making the tablets safe for use. This activity proved effective in enhancing students' knowledge and skills, and demonstrated that industrial waste can be utilized to produce valuable pharmaceutical products. The program supports the development of research-based and environmentally friendly pharmaceutical entrepreneurship among the younger generation.